House Vision - Cathelijne Nuijsink (Footprint)
The design of the detached house has been at the core of architectural developments in post-Second World War Japan and the subject of a lively discussion among architects about what makes a good home at a particular moment. Alongside the continuous production of houses, architects actively proposed new ways of living that contrasted with what was increasingly becoming a uniform housing stock based on mass fabrication. However, the intensification of neoliberal policies after a decade of severe economic crisis in the 1990s drove architects towards social involvement once again, initiating a housing trend based on sharing, renovation and re-use of the existing housing stock. This essay will highlight the work of the House Vision think-tank and full-scale building exhibitions – initiated in 2011 by Japanese designer and art director Kenya Hara – as one response to the socio-economic and political conditions after the neoliberal turn. Similar to the efforts of independent architects in recent decades, House Vision aims to generate awareness in society about alternatives to mainstream housing options. Yet what makes this initiative different is that it is not an individual effort but a collaborative project between designers and industries to push the latest technologies in home electronics, energy and mobility devices into new architectural forms.